Annual Plan 2000-2001 (Detailed Proposals) Volume III Government of Haryana - Planning Commission (Planning Commission, 2000)
In view of the guidelines issued by the Planning Commission Government of India, the focus is to be placed on seven basic minimum service which include Primary Education and Mid-Day-Meal programme in Primary schools during 9th Five Year Plan. Accordingly the State Government is determined to achieve universalization of Primary Education by the end of 9th Five Year Plan. The main emphasis would be on enrolment retention , qualitative improvement and provision of infrastructural facilities. According to 1991 census, the project population in the 6-10 age group would be 24.97 lacs by the end of 2001—2002. In order to achieve the target of universalization enrolment equivalent to 120% will have to be enrolled in Primary classes by the end of 9th Five Year Plan. the enrolment targets fixed for 8th Five Year Plan were based on the basis of 1981 census projected population in age 6-10.
Planning Department, Government of Haryana